Keterwakilan Perempuan pada DPRD Kabupaten Bangka Tahun 2014-2019: English - Oktari, Rinda (Jurnal Ilmu Administrasi Negara, 2020)
This research discusses about the representation of women in Bangka District in 2014-2019 to provide information about gender's inclusion in the political recruitment in the Bangka District that effect has not fulfilled its quota 30% representation of women in parliament, so that the research can provide solutions for the increased representation of women in the Bangka District. This research is a case study research done using a qualitative method. Research results suggest that the representation of women should be increased by a clear law enforcement act in the recruiting process, a social structure that involves female politicians in political parties and in parliament, mandated to pursue gender justice, and political education to cadre, future legislatif candidates and communities must be properly implemented by political and government parties so that increased representation of women can be achieved.